Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1111/epi.12098
|View full text |Cite
|
Sign up to set email alerts
|

Default mode network connectivity indicates episodic memory capacity in mesial temporal lobe epilepsy

Abstract: SUMMARYPurpose: The clinical relevance of resting state functional connectivity in neurologic disorders, including mesial temporal lobe epilepsy (mTLE), remains unclear. This study investigated how connectivity in the default mode network changes with unilateral damage to one of its nodes, the hippocampus (HC), and how such connectivity can be exploited clinically to characterize memory deficits and indicate postsurgical memory change. Methods: Functional magnetic resonance imaging (fMRI) resting state scans a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

23
103
3
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(130 citation statements)
references
References 47 publications
23
103
3
1
Order By: Relevance
“…Our results are consistent with those of previous studies that reported decreased iFC between the PCC and the epileptogenic hippocampus or mesial temporal lobe in patients with left MTLEϩHS. 10,31 In addition, we observed increased iFC on the right side in the same group of patients (On-line Table). Bettus et al 32 investigated iFC between the hippocampus and other limbic structures on the healthy side in a group of patients with unilateral MTLE 32 ; they reported increased iFC between the right hippocampus and the right temporal pole and right amygdala in patients with left MTLE.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Our results are consistent with those of previous studies that reported decreased iFC between the PCC and the epileptogenic hippocampus or mesial temporal lobe in patients with left MTLEϩHS. 10,31 In addition, we observed increased iFC on the right side in the same group of patients (On-line Table). Bettus et al 32 investigated iFC between the hippocampus and other limbic structures on the healthy side in a group of patients with unilateral MTLE 32 ; they reported increased iFC between the right hippocampus and the right temporal pole and right amygdala in patients with left MTLE.…”
Section: Discussionsupporting
confidence: 65%
“…9 The resting-state fMRI studies have shown decreased iFC between the epileptogenic hippocampus and the PCC in patients with unilateral MTLEϩHS, suggesting that this functional metric represents an altered functional pathway of the epileptic network. 10,11 Taken together, hippocampus-PCC connectivity (both structural and functional) is a potential pathway of the epileptic network in unilateral MTLEϩHS. Bernasconi et al 12 reported that volume loss in the hippocampus was related to epilepsy duration in patients with unilateral MTLEϩHS.…”
mentioning
confidence: 99%
“…This network is important in TLE because of its inclusion of the hippocampus (HC) and possible association with the episodic memory impairments observed in patients with refractory TLE (Holmes et al, 2012;McCormick et al, 2013). These diffuse, extratemporal reductions in the DMN agree with the diffuse structural impairments observed in the gray and white matter of patients with refractory TLE (Bernhardt et al, 2010;McDonald et al, 2008;Pittau et al, 2012).…”
mentioning
confidence: 62%
“…Another method of seed analysis is by correlating the signal between two, or multiple, regions of interest. Using such a method, the connectivity was found to be reduced between the lesional hippocampus and the posterior DMN in TLE 38 . On the other hand, ICA is data driven without a pre-existing hypothesis and delineates spatio-temporally distinct networks within the resting state brain.…”
Section: Discussionmentioning
confidence: 99%